Propensity to seek healthcare in different healthcare systems: analysis of patient data in 34 countries. Issue 1 (June 2015) - van Loenen, Tessa; van den Berg, Michael; Faber, Marjan; Westert, Gert
Abstract Background Some people have a lower threshold to seek care for certain symptoms than others. This study aims to investigate what factors are associated with patients' propensity to seek care. In addition, this study explores whether patients' propensity to seek care is associated with their actual health care utilization. We hypothesized that higher scores for propensity to seek care will lead to more general practitioners (GP) consultations, but to lower rates of avoidable hospitalization. Methods Propensity to seek care and GP utilization were measured by the Patient Experience Questionnaire of the QUALICOPC study, a survey among 61, 931 patients that recently visited GP services in 34 countries. Propensity to seek care was estimated by two questions: one question focusing on health care seeking behavior for serious symptoms and the other question focused minor complaints. Data on country level rates of avoidable hospitalization for CHF, COPD, asthma and diabetes were obtained from the OECD health care quality indicators project. Results Beside patient characteristics, various organizational factors, such as better accessible and continuous primary care, and better experienced communication between patient and GPs was associated with a higher propensity to seek care for both severe and minor complaints. A higher propensity to seek care was associated with a slightly higher health care utilization in terms of GP visits, with no differences between the severity of the experienced symptoms (OR 1.08 for severe complaints and OR 1.05 for minor complaints). At country level, no association was found between propensity to seek care and rates of avoidable hospitalization for CHF, COPD, asthma and diabetes, possibly due to low statistical power at country level. Conclusions The organization of primary care and patients' perceived communication with their GP were found to be highly correlated with patients' decision to seek health care for minor or severe complaints, suggesting that characteristics of healthcare systems directly influence patients' care seeking behavior, potentially leading to overuse or underuse of health services. However, we also observed that patients' propensity to seek care is only weakly associated with more GP use.